2009
DOI: 10.1590/s1679-62252009000100005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental variables and anthropogenic perturbations on stream fish assemblages, Upper Paraná River, Central Brazil

Abstract: The Ouvidor River, a tributary of the Upper Paraná River, drains areas covered by cerrado vegetation in Central Brazil. We collected data for environmental variables (water temperature, dissolved oxygen, pH, conductivity, turbidity, water velocity, luminosity, channel substrate and width) and anthropogenic perturbations (industry, reservoirs, urban areas) that may structure the fish assemblage in ten stream sites of the Ouvidor River basin. In each stream we delimited one 50 m long site where fish were capture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 36 publications
0
7
0
5
Order By: Relevance
“…A interferência do pH sobre a composição das comunidades de peixes é relatada em vários trabalhos (ABES;AGOSTINHO, 2001;TUNDISI;TUNDISI, 2008;FIALHO et al, 2008;TEJERINA-GARRO, 2009). A grande abundância de Rivulus zygonectes e Aequidens sp.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A interferência do pH sobre a composição das comunidades de peixes é relatada em vários trabalhos (ABES;AGOSTINHO, 2001;TUNDISI;TUNDISI, 2008;FIALHO et al, 2008;TEJERINA-GARRO, 2009). A grande abundância de Rivulus zygonectes e Aequidens sp.…”
Section: Discussionunclassified
“…A maior quantidade média de clorofila "a" detectada nos córregos afluentes do Rio das Mortes pode estar associada a dois fatores principais, ambos associados a diminuição da mata de galeria desses córregos: primeiro, aumento da luminosidade na água (SIMPAÚBA-TAVARES et al, 1995;WEBSTER et Variáveis ambientais e a estrutura da comunidade de peixes al., 1995;) e segundo, maior entrada de nutrientes originários das pastagens, os quais, em conjunto podem determinar um acentuado acréscimo da produtividade primária em ambientes aquáticos (BASSOLI;ROLAND, 2005;DAVIES et al, 2008;TUNDISI;TUNDISI, 2008;TEJERINA-GARRO, 2009; ESTEVES, 2011) além disso, a menor acidez das água com pH médio próximo ao neutro diminuem o stress aumentando a produtividade das comunidades fitoplanctônicas (BIUDES;CAMARGO, 2008). Esse aumento na produção primária pode determinar o estabelecimento de algumas espécies de peixes que utilizam diretamente essas algas ou os detritos originário dessas como recurso alimentar (DAVIES et al, 2008;TUNDISI;TUNDISI, 2008), como algumas espécies que foram encontradas apenas nos córregos da bacia do Rio das Mortes: Steindachnerina amazonica, Cyphocharax spiluropsis, Hemiancistrus spilomma, Hypostomus sp.…”
Section: Discussionunclassified
“…With the combined factors such as water temperature, conductivity, pH, current speed, declivity, and the presence of pools and waterfalls, altitude is capable of creating an environmental gradient that exerts influence on the species richness in each region (Pouilly et al, 2006). Araújo & Tejerina-Garro (2009), found that pH, water velocity, channel width and water temperature strongly affected fish assemblages in upper Paraná tributaries. Using geomorphologic data, Súarez & Petrere-Júnior (2007) suggested altitude as the most important structuring factor to fish community in the Iguatemi River basin.…”
Section: Methodsmentioning
confidence: 99%
“…An increase in the number of species and numbers of individuals (densities) towards the downstream‐deforested site was recorded. Such a pattern has also been reported by several other studies that have examined longitudinal gradients of fish assemblages in both temperate (Rahel & Hubert, ) and tropical regions (Abes & Agostinho, ; Mazzoni et al ., ; Petry & Schulz, ; Araújo & Tejerina‐Garro, ; Hoeinghaus et al ., ). In the present stream, the increase in fish numbers at the fully‐removed riparian site 3 was basically due to the establishment of two opportunistic species, H. punctatus and P. maculicauda , that colonized this site with densities that accounted for >60% of biomass.…”
Section: Discussionmentioning
confidence: 99%